Pengaruh Pembelajaran Online Berbasis Kooperatif dan Outcome Based Education Terintegrasi Kearifan Lokal Terhadap Kemampuan Berfikir Kritis - Kumala Ratna Dewi; Dadi Setiadi; I Wayan Merta (Jurnal Pijar Mipa, 2021)
The ability to think critically is stated as an essential skill in 21st century society so it must be integrated into the learning process. Critical thinking can be implemented through the cooperative learning model and Outcome Based Education integrated with local wisdom. The inclusion of local wisdom in learning is a manifestation of the mandate of national education. The occurrence of the Covid-19 outbreak requires learning to be carried out online. The purpose of this study was to determine the effect of cooperative-based online learning and Outcome Based Education integrated local wisdom on critical thinking skills. The research method used the nonequivalent pretest-posttest control group design, the determination of the sample used purposive sampling technique, the data collection used a multiple choice test, and the data were analyzed using the MANOVA test using SPSS 16,0. The pre-test average test result of Critical Thinking ability in the experimental group was 37.5, while the control group score was 53,57. Furthermore, the Post-Test average of Critical Thinking ability of the experimental group was 67,14, while the control group was 57,5. The results of the Test Between Subject Effect analysis resulted in a significant value of critical thinking skills of 0,004. Based on these results, it can be stated that there is an effect of cooperative-based online learning and Outcome Based education integrated local wisdom on the critical thinking skills of students of SMAN 8 Mataram.